Application of polymeric drilling fluids for reducing wearing of drill bit - Rawal R.; Karmakar N.C.; Sharma S.K.; Krishnamoorthi S. (My University, 2025)
The drill bit or cutting tool is a very important part of the rock drilling operation, it is directly associated with the rate of penetration. Bit wearing has significant involvement of time, labor, and wealth. By identifying the effect of various machine and rock parameters on bit wearing, the optimum working condition can be adopted to achieve high drilling efficiency. In this experimental work, the rate of penetration and parameters of drilling fluids (i.e. type, additives, and concentration, etc.) were optimized to identify their respective impact on the bit wearing of impregnated core diamond bit. The study has been conducted on a laboratory rotary drilling setup. The role of aqueous solutions of carboxymethyl cellulose (CMC), guar gum (GG), and polyacrylamide (PAM) has been examined as polymeric drilling fluid additives on sandstone rock samples and compared with the results of tap water alone as drilling fluid. A significant decrement in bit wearing has been noticed with all additives and the maximum reduction of 70.02% was achieved with CMC fluid additive. © 2022 Indian Chemical Society